Silage of agricultural by-products for pigs feeding. Bibliography review - Caicedo, W.; Ruiz, María Vanessa; Quilligana, Jissela Estefanía; Aguiar, S. (Cuban Journal of Agricultural Science, 2023)
The silages of agricultural wastes constitute a novel technique for the use of these resources for a long time. The silage process is carried out through a controlled fermentation, which guarantees a food of optimum nutritional quality, able to reduce imports of conventional raw matters and minimize the costs of pigs feeding. The beneficial microorganisms developed in this medium help to improve the chemical, microbiological and sensorial characteristics of the fermented raw matter. The pigs which intake fermented by-products have better intestinal health due to the competitive exclusion process of the beneficial microorganisms, with the consistent increase of dry matter intake, weight gain, feed conversion, final weight and carcass quality. For this reason, in the developing countries the technique of the agricultural wastes silage is implemented and are evaluated the chemical characteristics of this food and their effect on microbiological, blood, productive and reproductive indicators of pigs. The objective of this review was to assess the results of the use of agricultural by-products in pigs feeding. Results of the chemical components of the silage, digestibility and productive indicators are showed in pigs from post-weaning, growing and fattening categories. Key words: alternative food, pigs, fermentation, efficient microorganisms, agricultural resources